Development of PVA/Fe3O4 nanocomposite membrane. (2021) - Mohanty, Sribidhya; Panwar, Varij; Khanduri, Priya
Abstract: Orgainc polymers in the polymer matrix are normally insulators. There is a huge demand for the production of conductive polymers, especially from the electronic industry. The insertion of highly conductive inorganic fillers into the polymer matrix is the most common way to improve the conductivity of a polymer. But to date, to achieve. High conductivity, high loading of the fillers is needed, sacrificing the lightweight, excellent processability and low cost of polymeric materials. The goal of this paper is to evaluate the effect of filler on various parameters such as dielectric constant, dielectric loss and conductive property of Polyvinyl alcohol (PVA)/Ferrous Ferric Oxide (Fe3 O4 ) for a frequency range varying between 20 Hz and 10 MHz. PVA/ Fe3 O4 nanocomposite was fabricated by using solvent casting method. Variation in properties was measured by impedance analyser. This paper concludes that on adding 0.8 gm of Fe3 O4 to PVA, the best results of conductivity, dielectric constant and dissipation factor. Relevant parameter like conductivity of the membranes was highly affected by Fe3 O4 content and the conductivity increases with increase in Fe3 O4 content. The addition of Fe3 O4 as a filler to polymer matrix enhances the mentioned parameters, mechanical strength and magnetic behaviour. The ohmic behaviour was analyzed by Cole-cole plot. The nanocomposite formed by PVA/ Fe3 O4 because of its parameters can be used in biomedical applications, drug delivery and biosensors.